Does Small-Scale Irrigation Affect Women’s Time Allocation? Insights from Ethiopia - Lee, Yeyoung; Bryan, Elizabeth; Ringler, Claudia (AgriLinks, 2024)
Women’s time use and overall work burden have gained attention from researchers and policymakers as an essential aspect of their empowerment; time is an important resource that women often lack, and women’s agency to allocate time to preferred activities is limited. Women are often heavily involved in unpaid domestic and agricultural activities driven by gender norms about the division of labor. They, therefore, have limited time to engage in income-generating activities.